A DEVELOPMENT STRATEGY FOR DAIRY GOAT FARMS IN BOGOR REGENCY - WEST JAVA - Cyrilla, L.; Purwanto, B. P.; Astuti, D. A.; Atabany, A.; Sukmawati, A. (Diponegoro University, 2016)
The objectives of present study were to formulate development strategies for dairy goat' farms that capable of supporting goat's milk agribusiness. Three medium scale dairy goat farms located in Bogor Regency which has population of more than 100 heads and has established more than 10 years were purposively selected for the study. Data were collected during February to May 2014. The design of this study was based on descriptive qualitative approach (rapid appraisal approach). Data were analized using internal factors evaluation (IFE) and external factors evaluation (EFE), strategic position and action evaluation (SPACE) matrix, and grand strategy matrix. It was revealed that dairy goat farms in Bogor Regency were located in quadrant I in SPACE matrix, which was on the aggressive strategy. Dairy goat farms have many resource advantages, despite facing various threats. The Grand Strategy Matrix analysis showed that dairy goat farms were in quadrant I. Dairy goat farms were in an excellent position to take advantage of the opportunities, overcome internal weaknesses and avoiding multiple external threats. The best strategies to be selected for dairy goat farms were market penetration and product development.